Physical and mechanical properties of dolomites related to sedimentary and diagenetic features – case study of the Upper Triassic dolomites from Medvednica and Samobor Mts., NW Croatia (Rudarsko-geološko-naftni zbornik, 2018)
Sedimentary and diagenetic features of Upper Triassic dolomites are determined and related to technical properties (apparent density, water absorption, open porosity and point load strength tested by Point Load Test, PLT) for possible use as building aggregate. Samples are taken from three quarries in the Medvednica and Samobor Mts., in the NW Croatia. Samples from the Ivanec Quarry are determined as the early-diagenetic dolomite (EDD), late-diagenetic dolomite (LDD) and “transitional” dolomite (TD). Samples from the Dolje Quarry are determined as the early-diagenetic dolomite (EDD) and late-diagenetic dolomite (LDD). The samples from the Gradna Quarry are determined as the late-diagenetic dolomites (LDD). According to the physical and mechanical properties, the best variety to use as a crushed stone or as an aggregate proved to be is the late-diagenetic dolomite from the Dolje Quarry. Samples from the Dolje Quarry have the lowest values of open porosity and water absorption and the highest values of apparent density and PLT, due to their sedimentary-diagenetic features.